Effects of six weeks of stable versus unstable multi-dimensional surfaces balance training on passing skills and balance performance in young male basketball players - AGOPYAN, ANİ (IMR PRESS, 2021)
Background and objective: Adolescence is a period when balance and coordination decrease as a result of rapid musculoskeletal growth. These changes may affect various sports-specific skills, including balance. This study aimed to examine the changes in balance performance and basketball passing speed in male youth basketball players following six weeks of balance training performed on unstable versus stable surfaces. Methods: Twenty-five male basketball players, mean age 15.53 +/- 0.57 years, participated in balance training on different surfaces (unstable surface (US, n = 13); stable surface (SS, n = 12)) for six weeks (2 days/week; 35 to 50 min/day, incrementally). Their physical characteristics, passing skills (passing accuracy and speed test) and balance performance (Y-Balance Test and The Closed Kinetic Chain Upper Extremity Stability Test) were measured. Results: The improvement rates for passing accuracy (effect size (ES) = 0.86, moderate, P < 0.001), lower extremity (ES right = 0.94, moderate, P < 0.001; ES left = 0.88, moderate, P < 0.001) and upper extremity (ES right = 1.01, moderate, P < 0.001; ES left = 0.94, moderate, P < 0.001) balance scores, upper extremity stability test power (ES = 0.89, P < 0.001) and the normalized scores (ES = 1.20, moderate, P < 0.001) of the US group were higher than those of the SS group. Passing speed significantly increased only in the US group (P < 0.028). Conclusion: A multi-dimensional surface training model improved balance performance and passing accuracy skills compared to a stable surface training model for male basketball players. US balance training may be used as a complementary training model to increase dynamic balance and passing accuracy skills for male basketball players.
Keywords: Upper limb stability; Lower limb stability; Y-Balance Test; Passing skills; Basketball; STAR EXCURSION BALANCE; STRENGTH; YOUTH; ADAPTATIONS; STABILITY; SPORTS; INJURY; ADOLESCENTS; RELIABILITY; PROGRAM